The Effect Of Combination Of Hyperbaric Oxygen And Propolis Therapies To Blood Vessels Diameter In The Tension Area Of Periodontal Ligament During Tooth Movement To Prevent Relaps - Dandy Bayu Angkasa; Pambudi Rahardjo**,; Maria Lisdiana Tandjung (Denta Journal Kedokteran Gigi, 2019)
Background: The mechanical force of orthodontic device causes occurrence of a tension and a pressure area in the periodontal ligament. In the tension area, an inflammatory response characterized by vasodilation of blood vessels will occur. The function of blood vessel is to flow blood and other nutrients to accelerate the periodontal ligament remodeling process, so that relapse can be prevented. Purosee: To determine the effect of combination of propolis 3%, 5% for 14 days and HBOT 2,4 ATA 3x30 minutes with 5 minutes interval for 7 days in the tension area of ​​the periodontal ligament as an effort to prevent relapse. Materials and Methods: A randomized post-test only control group design was used in this study. 42 male guinea pigs (cavia cobaya) are divided into 7 groups K- (without treatment), K + (using separator), P1 (using separator and propolis extract 3%), P2 (using separator and propolis extract 5%), P3 (using separator and hyperbaric oxygen therapy), P4 (using separator and combination of hyperbaric oxygen therapy and 3% propolis extract), and P5 (using separator and combination of hyperbaric oxygen therapy and 5% propolis extract) . Results: Data shows that mean of diameter of blood vessels increased from the smallest K- (41,8417±0,84511), K+(61,77±1,254482), P1(72,5983±0,68869), P2(73,2333±1,24481), P3(74,2583± 0,62030), P4(91,47±0,76585), to the largest in P5(91,5483±0,96178). One-way Anova and LSD test showed significant differences in blood vessels diameter (p <0.05). Conclusion: The combination of propolis 3% and 5% and HBOT have significant effect in increasing blood vessels diameter in the tension area of ​​the periodontal ligament.